Analysis of Factors Influencing Compliance with Electronic Medical Record Documentation by Nurses and Midwives in the Inpatient Department of Siloam Hospital Bangka - Novia Winardi; Sumijatun Sumijatun; Dedy Nugroho; Thika Marliana (Journal of Ageing And Family, 2024)
Documentation using Electronic Medical Records (EMR) significantly improves the quality of patient medical record completion. Siloam Hospital Bangka has implemented EMR; however, several challenges have arisen in its application within the inpatient department. This study aims to analyze the factors influencing compliance with EMR documentation among nurses and midwives in the inpatient department, focusing on aspects of knowledge, motivation, supervision, and infrastructure availability. This study employs a quantitative approach with a cross-sectional design. The sample consists of 33 nurses and midwives in the inpatient department, selected using a total sampling technique. Data were collected through questionnaires and an audit observation checklist of inpatient medical records during the period from January 15 to January 22, 2025. Fisher’s exact test and multiple logistic regression were used to determine the dominant variables influencing documentation compliance. The research results indicate a significant relationship between knowledge (p-value = 0.000; OR = 184.000) and supervision (p-value = 0.000; OR = 46.000) with nurses and midwifes compliance in documentation. However, no significant relationship was found between motivation or infrastructure availability and documentation compliance. This study concludes that documentation compliance is influenced by knowledge and supervision, with knowledge being the most dominant factor. Since documentation compliance in electronic medical records supports the quality of healthcare services at Siloam Hospital Bangka, the hospital is recommended to implement regular training programs on the use of electronic medical records.